Effects of estrogen on the vascular system - Tostes,R.C. (2003)
The cardiovascular protective actions of estrogen are partially mediated by a direct effect on the vessel wall. Estrogen is active both on vascular smooth muscle and endothelial cells where functionally competent estrogen receptors have been identified. Estrogen administration promotes vasodilation in humans and in experimental animals, in part by stimulating prostacyclin and nitric oxide synthesis, as well as by decreasing the production of vasoconstrictor agents such as cyclooxygenase-derived products, reactive oxygen species, angiotensin II, and endothelin-1. In vitro, estrogen exerts a direct inhibitory effect on smooth muscle by activating potassium efflux and by inhibiting calcium influx. In addition, estrogen inhibits vascular smooth muscle cell proliferation. In vivo, 17ß-estradiol prevents neointimal thickening after balloon injury and also ameliorates the lesions occurring in atherosclerotic conditions. As is the case for other steroids, the effect of estrogen on the vessel wall has a rapid non-genomic component involving membrane phenomena, such as alteration of membrane ionic permeability and activation of membrane-bound enzymes, as well as the classical genomic effect involving estrogen receptor activation and gene expression.